Footprinting of linker histones H5 and H1 on the nucleosome. - Staynov, D Z (1988)
DNase I has been used to footprint the linker histones H5 and H1 on the nucleosome of chicken erythrocyte chromatin. Rate constants have been derived for digestion at the principal sites of attack on chromatosome length DNA (168 bp), located about 10 bp apart, and compared with those observed for linker histone-depleted chromatosomes. Complete protection was found for site S7 on the dyad axis and decreasing partial protection seen at symmetrically positioned sites on each side of S7. Strong, but not complete protection was noted at S14, the site corresponding to the end of the core particle, situated less than 1/4 of a turn away from the dyad. Uniform partial protection was observed for sites S2, S3, S4 and S10, S12 on the far side of the chromatosome. The simplest interpretation of these results is that the globular domain of H5/H1 is responsible for the protection at S7, whilst extended N- and C-domains give rise to the partial protection at sites away from the dyad axis.